Parathyroid adenoma: multimodal diagnosis capabilities: A retrospective study - Nikolai A. Ognerubov; Tatiana S. Antipova; Galina N. Abakumova (ZAO "Consilium Medicum", 2023)
Background. Primary hyperparathyroidism is a common endocrinological disease caused mainly by parathyroid adenoma. The main treatment method is surgery (parathyroidectomy). Therefore, the exact determination of adenoma localization is crucial. Aim. To evaluate the current possibilities of multimodal diagnosis of parathyroid adenomas. Materials and methods. A retrospective analysis of 49 patients with primary hyperparathyroidism aged 24 to 82 (median 57.9 years) was performed. Modern radionuclide and hybrid technologies were used for topical diagnosis and metabolic assessment of parathyroid adenomas: scanning, single-photon emission computed tomography, single-photon emission computed tomography combined with computed tomography, positron emission tomography combined with computed tomography with 18F-deoxyglucose and 18F-choline. The diagnosis of primary hyperparathyroidism was confirmed by a biochemical blood test: the level of parathyroid hormone and ionized and total calcium. Results. The study included 43 (87.8%) females and 6 (12.2%) males. The female/male ratio was 7.2:1. Most cases (78.1%) were the hypercalcemic type of primary hyperparathyroidism, and the normocalcemic type was diagnosed in 21.9% of patients. The mean parathyroid hormone level was 145.43 pg/mL, exceeding the reference values by 2.2 times. Parathyroid hormone concentration in patients with primary hyperparathyroidism was 156.38 pg/mL, and mean ionized and total blood calcium levels were 1.43 and 3.04 mmol/L, respectively. The asymptomatic type occurred in 76.7% of patients. The symptomatic type of hyperparathyroidism had 23.3%, manifested with nephrolithiasis, pancreatitis, and bone lesions. Parathyroid adenomas were more often located in the left lobe (42.9%). In 77.6% of patients with primary hyperparathyroidism, solitary adenomas were detected. Ectopia of the parathyroid glands was detected in 16.3% of patients, with intrathyroidal location in the left lobe being the most common. Rare locations include the anterior and posterior mediastinum and the esophageal wall. Conclusion. Modern diagnostic multimodal options based on radionuclide and hybrid technologies are crucial in the personalized treatment of primary hyperparathyroidism.